A Comparative Study of E-Learning Methods with Traditional Learning - Thakur, Ramesh (International Journal of Computer Sciences and Engineering, 2015)
E-learning based methods offer important teaching methods. E-learning offers pupils to have interactive e- content that comprises of multimedia. E-learning has great impact on learning process. The present work presents a comparative study of e-learning based methods with traditional teaching methods. The comparative study is performed on various user groups confirms the preference of e-learning based methods over traditional teaching methods. The feedback of the two methods is collected from different user groups consisting of researchers, students, instructors, and staff. E-learning based methods offered better feedback as compared to traditional teaching methods.